Relationship between gender and proactive work behaviour in the Kenya’s hotel industry - Shirandula, Duncan; Cheloti-Mapelu, Isabella; Sepula, Michael (African Journal of Tourism, Hospitality and Leisure Studies, 2017)
According to Kenya National Bureau of Statistics report, (2016), wage employment by industry and sex statistics indicate a majority of males employed in the modern sector than female with accommodation and food service industry registering 71 percent males and 29 percent female employees. This disparity extended to women in national decision-making category, with slight improvement from previous years. Participation of men and women in key decision making positions in the national assembly was at 19.8 per cent of total legislators. The share of female cabinet secretaries declined from 33.3 per cent in 2014 to 25.5 per cent in 2015. The disparities could be attributed to many other factors, among them the employers‟ perceptions on proactive behaviour between gender and gender role expectations. The purpose of this research paper was to test the difference in proactive work behaviour between the male and female employees working in Nairobi business hotels. The study employed a co-relational research design. From a target population of 190 front line employees, 127 formed the sample size for the study. Primary data was gathered from employees by use of self-administered questionnaires while secondary data was gathered from relevant books, hotel records, journals, publications and the internet. Reliability of data was tested using Cronbach‟s Alpha resulting in a value 0.804. One way ANOVA test was conducted to test the differences in proactive work behavior between male employees and their female counterparts. The findings of this study do not show a difference in proactive work behaviour between male and female employees (F 1.312; p˃0.05). Based on the combination of literature review with the results of this study, it is clear that gender does not restrain proactive behaviour at work. Adoption of work practices which support gender parity can offer a good first step towards innovation and being proactive at work place. Being “nice” to women by opening doors and offering to pay their bills, does not make women feel included. There is need to do more by reflecting on work patterns and policies so as to entrench measures which provide in-depth support of gender parity at work places.The researcher recommends that tourism and hospitality policy makers and regulators should develop national policies on employment which encourage flagship initiatives on gender equality as a key priority.
Keywords: Innovation; Proactive Work behaviour